Odpowiedź :
a) 3+2√3 + 2(3-√3) =3+2√3+6-2√3=9
b) 3+2√3 - 3-√3 =√3
c) 3-√3 - 3+2√3=√3
d) (3+2√3) x (2-√3) =6-3√3+4√3-6=√3
e) (3+2√3)² =9+12√3+12=21+12√3
b) 3+2√3 - 3-√3 =√3
c) 3-√3 - 3+2√3=√3
d) (3+2√3) x (2-√3) =6-3√3+4√3-6=√3
e) (3+2√3)² =9+12√3+12=21+12√3
a) 3+2√3 + 6-2√3 = 9
b) 3+2√3 - 3-√3 = √3
c) 3-√3 - 3+2√3 = 3-1√3 - 3+2√3 = √3
d) (3+2√3) x (2-√3) = 6-3√3+4√3-6 = -12√3
e) (3+2√3) do potegi 2 = 9+12√3+12
b) 3+2√3 - 3-√3 = √3
c) 3-√3 - 3+2√3 = 3-1√3 - 3+2√3 = √3
d) (3+2√3) x (2-√3) = 6-3√3+4√3-6 = -12√3
e) (3+2√3) do potegi 2 = 9+12√3+12